Grandmother spider : a Charlie Moon mystery - Doss, James D. (Doss, James D. Charlie Moon mystery., 2001)
Ute tribal cop Charlie Moon struggles with local superstitions and the "curse" of a Ute shaman as he digs for a rational reason for the disappearance of two men, with the help of his old friend, Police Chief Scott Parris.